Melanoma Identification and Management in an Unsheltered Male Using Teledermatology: Street Medicine Perspective - Emily Eachus; Taha Rasul; Armen Henderson (JMIR Publications, 2022)
Skin cancers are concerning for unsheltered people experiencing homelessness because of their high levels of sun exposure. Currently, there is little data on the prevalence of skin cancers in people experiencing homelessness. Skin diseases are often untreated in people experiencing homelessness due to a lack of access to specialized care. Miami Street Medicine (MSM) is an organization that provides people experiencing homelessness in the Miami Health District with medical care in a nonclinical street setting, near overpasses, sidewalks, and encampments. We present a case of an unsheltered 59-year-old male with a pigmented, 2 cm × 2 cm facial lesion that developed over several years. Through a teledermatology consultation, his lesion was highly suspicious of melanoma and further evaluation was recommended. Due to a lack of insurance, he could not be treated at any dermatology clinic. Coincidentally, 2 weeks later, he developed cellulitis of his lower extremity and was admitted to the local safety-net hospital through the emergency department. By coordinating with his primary inpatient team, MSM was able to include a biopsy of the lesion as part of his hospital stay. The results demonstrated melanoma in situ. The vital course of action was to ensure treatment before metastasis. After registration for insurance and follow-up with a surgical oncology team, he is weeks away from excision and reconstruction surgery. His unsheltered status made follow-up difficult, but MSM bridged the gap from the street to the clinical setting by incorporating teledermatology into patient evaluations and leveraging connections with community shareholders such as charitable clinics and volunteer physicians. This case also represents the barriers to care for cancer-based dermatologic outreach among people experiencing homelessness.